Associations between alcohol, smoking, socioeconomic status and comorbidities: Evidence from the 45 and Up Study. (23rd December 2013) - Bonevski, Billie; Regan, Tim; Paul, Chris; Baker, Amanda L.; Bisquera, Alessandra
Abstract Introduction and Aims. Understanding how tobacco, alcohol and mental health are related is important for developing population‐level policies and individual‐level treatments that target comorbidities. The current study aimed to examine sociodemographic characteristics and mental health comorbidities associated with the odds of using tobacco and harmful levels of alcohol concurrently. Design and Methods. Data were drawn from the 45 and Up Study, a large cohort study with 267 153 adults aged 45 years and over in New South Wales, Australia. Participants completed a survey assessing alcohol, smoking, psychological distress, treatment for depression and anxiety, and a range of socioeconomic status indicators. Univariate analyses and three multiple‐logistic regression models were used to determine associations with (i) tobacco but not alcohol use; (ii) alcohol but not tobacco use; and (iii) concurrent tobacco and risky levels of alcohol use. Results. Being female, younger, lower individual and area‐level socioeconomic status (SES) and depression and psychological distress were associated with tobacco use alone. Factors associated with alcohol use alone were older age, male gender, higher SES, and lower psychological distress and no recent depression treatment. Factors associated with concurrent risky alcohol consumption and tobacco use included being 45–64, being male, less education, earning <$30 000, being employed, and living in lower‐SES areas, treatment for depression, and high distress on the Kessler‐10. Discussion and Conclusions. Results suggest strong links between SES, treatment for depression, psychological distress, and concurrent tobacco and alcohol use. This has implications for public health policies and clinical treatment for tobacco and alcohol use, suggesting greater emphasis on addressing multiple health and social concerns. [Bonevski B, Regan T, Paul C, Baker AL, Bisquera A. Associations between alcohol, smoking, socioeconomic status and comorbidities: Evidence from the 45 and Up Study. Drug Alcohol Rev 2014;33:169–176]